2008
DOI: 10.1097/bcr.0b013e3181667963
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Hypercromic Palmar Graft With Split-Thickness Instep Plantar Graft—Case Report

Abstract: The plantar skin is the best donor site for grafting third-degree burn wounds onto volar aspect of hands and digits. In children, however, it is difficult to harvest the instep for a split-thickness graft. Most of these cases are treated with full-thickness or split-thickness skin grafts and dyspigmentation of the grafted area becomes a reality. We present a case of full-thickness graft hyperpigmentation that was treated with instep plantar graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…The plantar surface of the foot consists of glabrous skin, which seems the best possible match in colour, texture and strength for the palmar skin, and it was therefore considered a reliable option for coverage in the paediatric palm (Friel et al., 2015). The final outcome of split-thickness instep skin grafting to the palm has been reported to be superior to the results of full-thickness skin transplantation (Friel et al., 2015; Teles et al., 2008). Some authors have suggested this method to be applied exclusively in adolescents and small children, because more donor site complications leading to prolonged hospital stays, pain and problematic scars were reported in adults (Ward and Ecclestone, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…The plantar surface of the foot consists of glabrous skin, which seems the best possible match in colour, texture and strength for the palmar skin, and it was therefore considered a reliable option for coverage in the paediatric palm (Friel et al., 2015). The final outcome of split-thickness instep skin grafting to the palm has been reported to be superior to the results of full-thickness skin transplantation (Friel et al., 2015; Teles et al., 2008). Some authors have suggested this method to be applied exclusively in adolescents and small children, because more donor site complications leading to prolonged hospital stays, pain and problematic scars were reported in adults (Ward and Ecclestone, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…9). 12,13 Hair growth in such grafts leads to further mismatch. Hyperkeratosis, marginal hypertrophic scarring, fissuring, and breakdown are further possible complications.…”
Section: Discussionmentioning
confidence: 98%
“…In previous studies that aimed to resurface digital and palmar wounds, full‐thickness skin grafts or thick split‐skin grafts were harvested, which led to significant donor site morbidity, including prolonged healing, hypertrophic scarring, hyperpigmentation, or a requirement for secondary skin grafting of the donor site . A modified surgical method was reported recently, in which 2 layers of plantar skin grafts were harvested from the same site and the first‐harvested split‐thickness skin graft was returned to the original donor site .…”
Section: Discussionmentioning
confidence: 99%